Kebijakan Pemerintah terhadap Masyarakat Terdampak Covid-19 - Sirait, Bernad Martua; Kusmanto, Heri; Situmorang, Tony P. (PERSPEKTIF, 2024)
The Government's policy on Large-Scale Social Restrictions Guidelines has resulted in many Online Motorcycle Taxi drivers being unable to operate optimally. This paper examines the impact of the Government Policy on Guidelines for Large-Scale Social Restrictions on the operations of Online Motorcycle Taxi drivers, especially in the context of a 68 percent decline in the online transportation sector's revenue in 2020, as reported in the e-Conomy SEA report. This research highlights President Joko Widodo's speech on March 24, 2020 which provides stimulus to MSMEs, including motorcycle taxi drivers and taxi drivers, with a credit restructuring policy as one of its implementations. Using the Top-Down Policy Implementation Theory approach (M.S. Grindle), this paper uses a qualitative descriptive analytical method to analyze the implementation of the policy. The findings of the paper show that although online motorcycle taxi drivers feel helped by the absence of installment payments during credit restructuring, there is still hope to eliminate additional costs such as insurance fees, fiduciary fees, and penalty fees to support the implementation of the policy more effectively.